A The Analysis of Problem-Solving Ability by Considering Students’ Curiosities in the 7E Learning Cycle Model with Ethno-Mathematical Nuances - Nofal, Agus; Zaenuri, Zaenuri; Cahyono, Edy (Universitas Negeri Semarang, 2021)
This study aims to describe students' problem-solving abilities by considering their curiosities. The subjects in this study are determined based on the analysis of the results of the Curiosity Inventory in class VIIIA students of SMP N 1 Bandungan, Semarang Regency. Students are grouped into two types, namely the type of Epistemic Curiosity (EC) and the type of Perceptual Curiosity (PC). The EC group are taken by two students, namely a weak (Lemah) EC (ECL) and a strong (Kuat) EC (ECK), as well as the PC group taken by two students, namely a weak PC (PCL) and a strong PC (PCK). This research is a mixed method research with a sequential explanatory design. The data collection techniques use questionnaires, tests and interviews. The effectiveness is analyzed based on (1) the average similarity test; (2) completeness test and average difference test. Based on data analysis, the results of tests and interviews show that the ECL type students are able to understand problems, plan solutions and carry out the completion plans, but are unable to check again. ECK type students are able to understand the problem until it checks again properly. The PCL type students are able to understand the problem but are less able to plan solutions and carry out the completion plan and are unable to check again. The PCK type students are able to understand problems, plan completion plans and carry out completion plans but are less able to check again.